2020
DOI: 10.1155/2020/6015283
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Potential and Antimicrobial Resistance Profile of Staphylococcus aureus in Milk and Beef from the Northwest and Southwest Regions of Cameroon

Abstract: Staphylococcus aureus is a major foodborne pathogen and commensal of the skin and mucous membranes of animals and humans. Its virulence relies on the production of a variety of toxins resistant to denaturing conditions. Increasing reports of S. aureus food poisoning and contamination of foods of animal origin elsewhere necessitates the investigation of these foods in Cameroon, to implement safety measures. This cross-sectional study evaluated S. aureus contamination in milk and beef in the Northwest and Southw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
(58 reference statements)
2
12
2
Order By: Relevance
“…They were most often resistant to erythromycin (62%), ampicillin (62%) and oxacillin (46%) [15]. On the other hand, Bissong MAE (2020), analyzing the resistance of staphylococcus aureus, showed 39 isolates S. aureus from 289 microorganisms [16]. In both of these studies, staphylococci were characterized by high resistance to erythomycin (82% -Bissong, 62% -Mphahlele), and in the case of Bissong MAE work, there was high resistance to vancomycin (80%) and tetracycline (76%).…”
Section: Discussion Of the Problemmentioning
confidence: 99%
“…They were most often resistant to erythromycin (62%), ampicillin (62%) and oxacillin (46%) [15]. On the other hand, Bissong MAE (2020), analyzing the resistance of staphylococcus aureus, showed 39 isolates S. aureus from 289 microorganisms [16]. In both of these studies, staphylococci were characterized by high resistance to erythomycin (82% -Bissong, 62% -Mphahlele), and in the case of Bissong MAE work, there was high resistance to vancomycin (80%) and tetracycline (76%).…”
Section: Discussion Of the Problemmentioning
confidence: 99%
“…Furthermore, the study revealed that 71% and 67% of E. coli were resistant to tetracycline in milk and drinking water respectively, while less resistance (20%) was observed in green fodder. Antibiotic resistance can be transferred to humans via the food chain through consumption of antimicrobial residues or contamination of resistant bacteria in animal products [10].…”
Section: Antibiotic Susceptibility Of Escherichia Coli Strainsmentioning
confidence: 99%
“…Antibiotic susceptibility testing revealed 95% resistance to β-lactamases, 78% to Macrolides, 42% to Glycopeptides, 16% to Quinolones, 5% to Aminosides and Cotrimoxazole and 0% to Chloramphenicol [9]. Another study on the pathogenicity and antimicrobial resistance profile of Staphylococcus aureus in beef and milk in the North West and South West regions of Cameroon revealed that the majority of isolates were resistant to erythromycin (82%), vancomycin (80%), tetracycline (76%) and oxacillin (74%) [10]. The increasing prevalence of antibiotic resistance (AR) is a global concern and the role of raw milk in the spread of AR is unclear [4].…”
Section: Introductionmentioning
confidence: 99%
“…Kesah et al [12] reported 21.3% (21/127) MRSA prevalence; while Njoungang et al [13] documented 13.9% (28/201) from clinical samples in Yaounde. Also, Bissong et al [14] reported 13.2% from clinical samples in Douala and equally documented that 37 (74%) of the 50 S. aureus isolates identified from 289 samples (milk and beef) from the Northwest and Southwest Cameroon were MRSA [15]. All these studies identified MRSA based on phenotypic (oxacillin or cefoxitin screening) methods only.…”
Section: Introductionmentioning
confidence: 99%